Fault‐magma interactions during early continental rifting: Seismicity of the Magadi‐Natron‐Manyara basins, Africa. (30th October 2017) - Weinstein, A.; Oliva, S. J.; Ebinger, C. J.; Roecker, S.; Tiberi, C.; Aman, M.; Lambert, C.; Witkin, E.; Albaric, J.; Gautier, S.; Peyrat, S.; Muirhead, J. D.; et al.
Abstract: Although magmatism may occur during the earliest stages of continental rifting, its role in strain accommodation remains weakly constrained by largely 2‐D studies. We analyze seismicity data from a 13 month, 39‐station broadband seismic array to determine the role of magma intrusion on state‐of‐stress and strain localization, and their along‐strike variations. Precise earthquake locations using cluster analyses and a new 3‐D velocity model reveal lower crustal earthquakes beneath the central basins and along projections of steep border faults that degas CO2 . Seismicity forms several disks interpreted as sills at 6–10 km below a monogenetic cone field. The sills overlie a lower crustal magma chamber that may feed eruptions at Oldoinyo Lengai volcano. After determining a new ML scaling relation, we determine a b ‐value of 0.87 ± 0.03. Focal mechanisms for 65 earthquakes, and 13 from a catalogue prior to our array reveal an along‐axis stress rotation of ∼60° in the magmatically active zone. New and prior mechanisms show predominantly normal slip along steep nodal planes, with extension directions ∼N90°E north and south of an active volcanic chain consistent with geodetic data, and ∼N150°E in the volcanic chain. The stress rotation facilitates strain transfer from border fault systems, the locus of early‐stage deformation, to the zone of magma intrusion in the central rift. Our seismic, structural, and geochemistry results indicate that frequent lower crustal earthquakes are promoted by elevated pore pressures from volatile degassing along border faults, and hydraulic fracture around the margins of magma bodies. Results indicate that earthquakes are largely driven by stress state around inflating magma bodies. Key Points: Lower crustal earthquakes along projections of steep border faults Local stress field rotation facilitates strain transfer from border fault to central zone of magma intrusion Volatile release from magma intrusion localizes strain in early‐stage rift systems